Retinal laser lenses: magnification, spot size, and field of view. Issue 3 (March 1990) - Mainster, M A; Crossman, J L; Erickson, P J; Heacock, G L
Abstract : Proper use of ophthalmoscopic contact lenses for retinal photocoagulation requires knowledge of their comparative magnification, spot size, and field of view. We determined these parameters for four commonly used lenses, using data measured from optical components of the lenses and a commonly used photo-coagulator slit-lamp and spot size changer. A Krieger lens has 8% more working field of view and 29% less magnification than a Goldmann lens. A Panfundoscope lens has 84% more working field of view and 24% less magnification than a Goldmann lens. A Mainster lens has 58% more working field of view and 3% more magnification than a Goldmann lens. For Goldmann, Krieger, Panfundoscope, and Mainster lenses, respectively, retinal spot size is 8%, 53%, 41%, and 5% greater than photo-coagulator spot size settings. The field of view of each lens is increased in myopic and decreased in hyperopic patients. Anterior segment irradiance is higher than retinal irradiance for 1000 microns spot size settings with a Panfundoscope or Mainster lens, and this setting should be avoided, especially in patients with hazy ocular media.